PERTANGGUNG JAWABAN PIDANA KORPORASI DALAM KEJAHATAN EKONOMI - Umi Enggarsasi (Perspektif, 2002)
In a modernization process, especially in economics, corporations have been convinced as a main characteristic of modern industry community. The extension role of corporations may arouse many distractions that discourage the economics development itself. In case of legal responsibility, corporations should have done illegal action referring to the regulations. The likely the most appropriate legal sanction for a corporation is economical and administrative sanction.